English Teacher Insights on Strategies to Reduce Boredom in Online Grammar Class - Arifin, Syamsul; Imam Wahyudi Karimullah; Elchin Gashimov (Institut Agama Islam Negeri Palopo, 2025)
This study investigates empirical investigations regarding teacher insights in reduce boredom an online grammar class. This research is still resolved in most of online setting. Boredom is one of the most challenges in online course faced by English teachers even the students. As learning environments become more digital, it's becoming increasingly difficult to keep students interested. Hence, the researcher finds a number of educational strategies which successfully raise students’ engagement and interest. This study explored qualitative procedures to properly comprehend teacher insights in reduce boredom in online grammar class. The participants for this research included three teachers in English course in Pare. Data collection methods included with semi-structured interview and even observation in online class. Data analysis was used to examine the interview and focus group data. The result shown that teachers believe incorporating these strategies are critical to enhancing learning outcomes in general as well as lowering boredom. There are two interactive teaching strategies on teacher insights an online grammar class are interactive discussion and interactive Quizizz tool. In consequence, incorporating those interactive strategies into online grammar class as affective approach dependent on the teachers' expertise. Providing insights for teachers looking to improve students’ engagement in online classrooms, this case advances the understanding of effective online teaching approaches.